Geologia do alvo e da mina Sol Nascente, município de Rio Crespo, Rondônia - Socchor, Caio Sérgio [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Eight Mesoproterozoic granite suites are recognized in the Rondônia Tin Province, called Serra da Providência Intrusive Suite (1606-1532 Ma), Rio Crespo Intrusive Suite (1500 Ma), St. Anthony Intrusive Suite (1406 Ma), Teotonio Intrusive Suite (1387 Ma ), Santa Clara Intrusive Suite (1082-1074 Ma) and Younger Granites of Rondônia Intrusive Suite (998-974 Ma), represent successive magmatic type A (anorogenic) and the intra-plate basement rocks intruded in the metamorphic complex named Jamari separated into two distinct lithologic associations, a ortogneiss (U-Pb from 1.76 to 1.73 Ga) and a paragneiss (1675 + / - 12 Ma). Tin mineralization are widely found in the Tin Province and are associated with granitic intrusions known Mesoproterozoic more closely with the last two magmatic events, represented by the Santa Clara and Younger Granites of Rondônia. The tin mineralization are of primary and secondary, with the primary form deposits of different structural styles and is presented in the form of endo-or exogreisens, veins, stockworks and pegmatites. The secondary mineralization are related to natural processes of weathering and erosion of primary rocks, leading to placer deposits classified as colluvial, eluvial and colluvial-alluvial. The Target Alvo Sol Nascente is located in the central-eastern Rondônia Tin Province and has basement rocks of the metamorphic-magmatic region represented by Jamari Complex intrusive suites and Sierra Providence and Rio Crespo. The last tectonic event spa in the area was responsible for the intrusion of Younger Granites of Rondônia (São Carlos and Caripuanã Massifis). The anomalous levels of tin, sufficient to operate (Mina Rising Sun), indicate that there was possibly mineralization event, evidenced by pegmatite veins well defined, easily found relatively close to mine. Plaque deposits associated with Quaternary sedimentary sequences can also be observed

Oito suítes graníticas mesoproterozóicas são reconhecidas na Província Estanífera de Rondônia, denominadas de Suíte Intrusiva Serra da Providência (1.606 – 1.532 Ma), Suíte Intrusiva Rio Crespo (1.500 Ma), Suíte Intrusiva Santo Antônio (1.406 Ma), Suíte Intrusiva Teotônio (1.387 Ma), Suíte Intrusiva Santa Clara (1.082 – 1.074 Ma) e Suíte Intrusiva Granitos Últimos de Rondônia (998 – 974 Ma), representam sucessivos episódios magmáticos do tipo A (anorogênicos) e intra-placa, intrudidas nas rochas do embasamento metamórfico denominado Complexo Jamari, separado em duas associações litológicas distintas, uma ortoderivada (U-Pb 1,76 – 1,73 Ga) e uma paraderivada (1675+/- 12 Ma). Mineralizações de estanho são amplamente encontradas na Província Estanífera e são reconhecidamente associadas às intrusões graníticas mesoproterozóicas, mais estreitamente com os dois últimos eventos magmáticos, representados pela Suíte Santa Clara e Granitos Últimos de Rondônia. As mineralizações de estanhos são de origem primária e secundária, sendo que, as primárias formam depósitos de diferentes estilos estruturais e apresenta-se na forma de endo ou exogreisens, veios, stockworks e pegmatitos. As mineralizações secundárias estão relacionadas a processos naturais de intemperismo e erosão das rochas primárias, originando depósitos de placeres classificados em coluvionares, colúvio-eluvionares e aluvionares. O Alvo Sol Nascente localiza-se na porção centro-leste da Província Estanífera de Rondônia e apresenta rochas do embasamento metamórfico-magmático da região representadas pelo Complexo Jamari e das suítes intrusivas Serra da Providência e Rio Crespo. O último evento tectno-termal reconhecido na área foi responsável pela intrusão da Suíte Granitos Últimos de Rondônia (Maciço de São Carlos e Caripuanã)... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cassiterita; Pegmatitos; Estanho; Rochas igneas; Rio Crespo (RO); Cassiterite; Pegmatites; Tin; Igneous rocks